General Fuzzy Graphs - Nishad T.M.; B Mohamed Harif; Talal Ali Al-Hawary (Ratio Mathematica, 2023)
Fuzzy graphs have many applications in database theory,neural networks and decision making problems.Literature survey shows that in the exisiting definition of fuzzy graph the membership value on links is always less than or equal to the minimum of membership values on the corresponding nodes.This restriction brings a difficulty to address some practical problems where the membership value on links does not depend on that of corresponding nodes.So there exists a gap in literature of fuzzy graphs.In this article we have developed general fuzzy graph and general weak fuzzy graphs and have proved some properties of general weak fuzzy graphs.